THE ROLE OF DISABILITY INCLUSIVE DEVELOPMENT IN MODERATING THE EFFECT OF TRAINING AND COMPETENCE ON HEALTH WORKER SERVICE PERFORMANCE - Rudi Wibowo; Imran Syah; Erna Nur Faizah; Firyal Fasihah (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: Healthcare services for people with disabilities face challenges related to accessibility, healthcare worker readiness, and the implementation of inclusive services. This study aims to examine the effect of training and competency on healthcare service performance and to analyze the moderating role of Disability Inclusive Development (DID). Research Methodology: This study employed a quantitative research approach using SEM-PLS for data analysis. The research sample consisted of 125 healthcare workers at Muhammadiyah Babat Hospital, selected through a census sampling technique. Data were collected and analyzed to examine the relationships among training, competency, Disability Inclusive Development (DID), and healthcare service performance. Results: The results show that training and competency have a positive and significant effect on healthcare service performance, with competency as the most dominant factor. DID also has a significant effect on service performance and strengthens the relationship between training, competency, and service performance. Conclusions: Improving healthcare worker competency, supported by effective training programs and disability-inclusive approaches, is essential for enhancing the quality of inclusive healthcare services. Limitations: The study is limited by the R-square value of 0.545, indicating that training, competency, and DID explain 54.5% of the variation in healthcare worker service performance, while other factors remain unexplored. Contributions: This study contributes theoretically by integrating training, competency, and DID into an SEM-PLS framework. Practically, it provides recommendations for hospital management to develop inclusive training, strengthen healthcare worker competency, and improve disability-friendly service policies